2018
DOI: 10.3390/recycling3040055
|View full text |Cite
|
Sign up to set email alerts
|

A Biowaste Treatment Technology Assessment in Malawi

Abstract: In the city of Blantyre, much of the generated municipal waste is biowaste, typically mixed with other waste fractions and disposed at the city’s dumpsite. Energy and nutrients could be recovered; however, with many biowaste options available, choosing what technology to implement is difficult. Selecting Organic Waste Treatment Technology (SOWATT) is a tool that supports decision making for selecting a biowaste treatment option considering social, technical, and environmental aspects. SOWATT was used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…A substantial part of the studies concerns wastewater treatment technology selection (Ilangkumaran et al, 2013;Fetanat et al, 2021;Aydiner et al, 2016;Sadr et al, 2013;Meerholz & Brent, 2013;Salamirad et al, 2021 ) with the use of MCA methods. Some authors address problems of waste disposal technology selection (Jiang et al, 2015;Govind Kharat et al, 2019), biowaste treatment technology (Mpanang' ombe et al, 2018) or food waste technology (Chadderton et al, 2017). Many studies address interdisciplinary subjects, for example, sustainable waste disposal management (Torkayesh et al, 2021;Kharat et al, 2020).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…A substantial part of the studies concerns wastewater treatment technology selection (Ilangkumaran et al, 2013;Fetanat et al, 2021;Aydiner et al, 2016;Sadr et al, 2013;Meerholz & Brent, 2013;Salamirad et al, 2021 ) with the use of MCA methods. Some authors address problems of waste disposal technology selection (Jiang et al, 2015;Govind Kharat et al, 2019), biowaste treatment technology (Mpanang' ombe et al, 2018) or food waste technology (Chadderton et al, 2017). Many studies address interdisciplinary subjects, for example, sustainable waste disposal management (Torkayesh et al, 2021;Kharat et al, 2020).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The study reported the application of different MCDM techniques, mainly focusing on selecting WtE generation technologies based on environmental, economic, technical, and socio-political [147]. The reviewed literature evaluates the technologies that could efficiently convert biomass by applying technologies WTE to produce different energy carriers [147][148][149][150][151]. However, few studies in the literature applied MCDM, focusing on evaluating and optimizing specific WTE technologies based on the produced biochar properties and their applications.…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
“…Economic impacts of AD: AD can be considered a more economically attractive FWM option than IVC [76] due to product revenue arising from the electricity generation (GBP 4/t FW) and the electricity exported to the grid (GBP 13/t FW) [46]. In the UK, the digestate has no market value and operators may force to pay users to take it away (GBP 4/t FW) [46].…”
Section: Sustainability Performance Of Off-site Fwm Processesmentioning
confidence: 99%